ANALYSIS OF STUDENTS’ ERROR IN USING PERSONAL PRONOUNS - Nurjanah Nurjanah (Deiksis, 2012)
This research was held in the first year of MTs Al-Hidayatussalafiyah. The samples of this research are 40 students. To get the data, I gave a pronoun test where students had to identify errors concerning subjective, objective, possessive adjective, and possessive pronouns. Data analysis shows that the students made a total of 248 errors which consist of 42 or 16.93 % errors in using subjective pronouns, 111 or 44.75% errors in using objective pronouns, 17 or 6.85% errors in using possessive adjectives, and 78 or 31.45 % errors in the use of possessive pronouns. Based on the percentage, it can be concluded that the students still find difficulties in learning personal pronouns.Key words: Errors, personal pronouns